Greening of the District Heating Systems—Case Study of Local Systems - Artur Wyrwa; Maciej Raczyński; Maciej Kulik; Oluwalana Oluwapelumi; Laura Mateusiak; Haoran Zhang; Marek Kempka (Energies, 2022)
The integration of renewable energy resources into district heating systems is gaining momentum across Europe, as heat producers are expected to work towards the EU Directive of Efficient District Heating and Cooling to achieve carbon neutrality by 2050. This paper studies the techno-economic implications of transforming conventional district heating systems of six locations in Poland, generating 8.5 PJ of heat annually, into sustainable and efficient district heating systems. These new systems consist of flat solar collectors integrated with seasonal pit thermal energy storages and gas heating plants, acting as flexible heat sources, covering residual heat demand and/or increasing the parameters of the working medium in the network. Using the IEA-TIMES software, two scenarios were considered, namely STAT and DYN. The results show that reaching a 20% share of heat production by solar thermal would demand extra construction of seasonal heat storage facilities with a total capacity of 197 TJ, which is approximately 4.5 times bigger than the largest seasonal heat storage located in Vojens, Denmark. The projected increase in the prices of natural gas and CO2 emission allowances accelerates the transformation of systems towards greater use of solar heating plants. In the period 2025–2050 the heat generation costs increase by ca. 65%. The contribution of the CAPEX and OPEX costs components are presented.